The Female and Egg of Salmoperla sylvanica (Plecoptera: Perlodidae) - Stark, Bill P. (Illiesia, 2006)
The first descriptions of the egg and female are provided for Salmoperla sylvanica Baumann & Lauck, a large perlodine stonefly known only from northernCalifornia. Comparisons are made with Oroperla, the apparent sister group for Salmoperla.
Keywords: insekti; Plecoptera; vrbnice; entomologija; favna; Kalifornija; California